PpCas9 from Pasteurella pneumotropica - a compact Type II-C Cas9 ortholog active in human cells - Fedorova, Iana; Vasileva, Aleksandra; Selkova, Polina; Abramova, Marina; Arseniev, Anatolii; Pobegalov, Georgii; Kazalov, Maksim; Musharova, Olga; Goryanin, Ignatiy; Artamonova, Daria; Zyubko, Tatyana; Shmakov, Sergey; et al. (Nucleic Acids Research, 2020)
CRISPR-Cas defense systems opened up the field of genome editing due to the ease with which effector Cas nucleases can be programmed with guide RNAs to access desirable genomic sites. Type II-A SpCas9 from Streptococcus pyogenes was the first Cas9 nuclease used for genome editing and it remains the most popular enzyme of its class. Nevertheless, SpCas9 has some drawbacks including a relatively large size and restriction to targets flanked by an 'NGG' PAM sequence. The more compact Type II-C Cas9 orthologs can help to overcome the size limitation of SpCas9. Yet, only a few Type II-C nucleases were fully characterized to date. Here, we characterized two Cas9 II-C orthologs, DfCas9 from Defluviimonas sp.20V17 and PpCas9 from Pasteurella pneumotropica. Both DfCas9 and PpCas9 cleave DNA in vitro and have novel PAM requirements. Unlike DfCas9, the PpCas9 nuclease is active in human cells. This small nuclease requires an 'NNNNRTT' PAM orthogonal to that of SpCas9 and thus potentially can broaden the range of Cas9 applications in biomedicine and biotechnology.
© The Author(s) 2020. Published by Oxford University Press on behalf of Nucleic Acids Research.
Keywords: Amino Acid Sequence; Base Sequence; CRISPR-Associated Protein 9/chemistry; CRISPR-Cas Systems; Cloning, Molecular; Clustered Regularly Interspaced Short Palindromic Repeats; Escherichia coli/genetics; Gene Editing/methods; Gene Expression; Genetic Vectors/chemistry; Genome, Bacterial; HEK293 Cells; Humans; Nucleic Acid Conformation; Pasteurella pneumotropica/enzymology; RNA, Guide, CRISPR-Cas Systems/chemistry; Recombinant Proteins/chemistry; Rhodobacteraceae/enzymology; Sequence Alignment; Sequence Homology, Amino Acid